Resource allocation with carrier aggregation in cellular networks : optimality and spectrum sharing using C++ and Matlab /: optimality and spectrum sharing using C++ and Matlab. ([2018]) - Shajaiah, Haya; Abdelhadi, Ahmed; Clancy, T. Charles
No abstract available